Drug utilization pattern and cost analysis of antidiabetic drugs among type 2 diabetic patients at a teaching hospital in South India: A prospective observational study - Sekar Kavitha; Anandabaskar Nishanthi; Vivekraj Navabalan; Shanthi Manickam; Anuranjani Dhamodharan; Girija Subramanian (Journal of Family Medicine and Primary Care)
Background: Type 2 diabetes mellitus (T2DM) significantly contributes to the global burden of chronic diseases. Rational prescribing and complete documentation are essential for optimizing therapeutic outcomes and ensuring continuity of care. Objective: To evaluate the drug prescribing pattern using the World Health Organization (WHO) core prescribing indicators, assess the completeness of prescription documentation, and analyse the cost of drug therapy among type 2 diabetic patients attending a teaching hospital in South India. Materials and Methods: We conducted a cross-sectional study among type 2 diabetic patients visiting the Department of General Medicine and audited the completeness of their prescriptions based on the presence of superscription, inscription, and subscription components. Prescribing trends were analysed using the WHO drug use indicators. The total cost of the drugs per prescription and the proportion attributed to antidiabetic drugs was calculated. Results: The average number of drugs per prescription was 4.5, percentage of drugs prescribed by generic name was 68.03%, and percentage of patients with injection prescribed was 58.3%. Percentage of patients prescribed with antibiotics was 21.2%, and 99.7% of drugs were prescribed from NLEM list. Conclusion: This study highlights areas for improvement, including the use of multiple medications, a relatively high rate of injectable prescriptions, and opportunities to enhance generic prescribing among diabetic patients in a teaching hospital in India. Multidisciplinary collaboration is essential for rational, cost-effective medication use and improved healthcare outcomes.